Construction of a 3D multiple network skeleton by the thiol-Michael addition click reaction to fabricate novel polymer/graphene aerogels with exceptional thermal conductivity and mechanical properties. Issue 42 (23rd October 2017) - Song, Shiqiang; Zhang, Yong
Abstract : Novel porous polymer/graphene composite aerogels with a multiple network structure, enhanced compressive properties and high thermal conductivity are first fabricated by adsorbing water vapour, reduction, and freeze-drying procedures. Abstract : Novel porous polymer/graphene composite aerogels with a multiple network structure, enhanced compressive properties and high thermal conductivity are first fabricated by adsorbing water vapour, reduction, and freeze-drying procedures. The aerogels are comprised of a copolymer of monomethacrylate terminated poly(dimethylsiloxane) and glycidyl methacrylate (PDMS–PGMA), polydopamine–reduced graphene oxide (PDA–rGO), and poly(3-mercaptopropyl)methylsiloxane (PMMS). PMMS as a crosslinking agent reacts with PDMS–PGMA and PDA–rGO by the thiol-Michael addition click reaction, resulting in the formation of unique multiple networks in the aerogels. An aerogel with a low graphene loading (2 wt%) exhibits optimal comprehensive performance, i.e. a high thermal conductivity (0.816 W m −1 K −1 ), high compressive stress at 50% compression ratio (3.4 MPa) and good oil-adsorption capacities. These outstanding properties of aerogels are attributed to the multiple networks and the interconnected PDA–rGO skeleton. The aerogels have potential applications in heat radiating elements, oil/water separators and high performance materials.